(untitled) (Experimental biology, 2020)
In accordance with the Concept for the transition of Kazakhstan to the "green economy", the main task in the field of fisheries development is to preserve the biological diversity of water bodies, where special attention is paid to the conservation of sturgeon species. In this regard, conditions are being created for the development of commercial fish farming, which will reduce the fishing load on natural reservoirs. Within the framework of the State Agro-Industrial Complex Development Program, the growth of aquaculture volumes is forecasted from 1.6 thousand tons in 2017 to 5 thousand tons by 2021 (https://strategy2050.kz/ru/news/51441/). Thus, the importance of aquaculture is increasing. The high density of individual species on farms leads to a sharp increase in the number of pathogenic microorganisms and the mass mortality of fish, which is why they are the most economically significant obstacle to the development of aquaculture. To reduce losses during the reproduction of water bodies, prophylactic or therapeutic measures are carried out almost universally using antibiotics, which are most often added to food. At the same time, residual content of antibiotics used in the treatment and prevention of bacterial infections is noted in food raw materials and products from aquaculture objects, which leads to the entry into the consumer’s body and the environment of various antibiotics used in different countries for commodity cultivation of objects. Thus, these antibiotics found in the human body, as well as in the environment stimulate the emergence of bacteria with multidrug resistance. Endolysins are a potential replacement for antibiotics with almost no side effects. Endolysins do not affect representatives of the normal microflora of the body. In addition, a very important aspect is the impossibility of developing resistance to them. Thus, endolysins have great potential in the fight against various pathogens, being an excellent alternative to antibiotics. Key words: aquaculture, bacterial diseases, antibiotics, bacteriophage, endolysin.